The Role of Onabotulinum Toxin Type A in the Management of Chronic Non-migraine Headaches - Jia, Cassie; Lucchese, Scott; Zhang, Fang; Govindarajan, Raghav (Frontiers in Neurology, 2019)
Objectives: FDA has approved Onabotulinum toxin type A (BoNTA) for prophylactic treatment of chronic migraines. Recent studies have explored its potential new indications, like treating post-traumatic headaches. Patients and Methods: This is a retrospective chart review of 717 patients, who had failed at least two prophylactic treatments and received BoNTA injections at University of Missouri Hospital from July 2014 to June 2017. Patient demographics, headache type, associated symptoms, prophylaxes tried were reported. Patient's pain severity (numeric pain scale) and frequency (number of headache days/month) pretreatment, at 6 months, and at 12 months were collected. Results: For a single headache type, post-traumatic headaches showed reduction in headache pain severity at 6 months (2.9±0.7) compared to pre-treatment (7± 0.7). Headache frequency for post-traumatic headaches was also reduced at 6 months (10.6±2.3) and 12 months (5.1±1.2) compared to pre-treatment (25±1.8). For pseudotumor cerebri headaches, pain severity at pretreatment was 6.4±0.6 compared to 2±0.8 at 6 months, and headache days reduced at 6 months (9.8±2.5) and 12 months (6±4) compared to pretreatment (26±2.9). Opioid use reduced by 67±55.4 at 6 months and 133.3±106.6 at 12 months in morphine equivalent units. Conclusions: Onabotulinum toxin type A is effective in treating multiple types of chronic non-migraine headaches.